Fabrication of Low-Twist and High-Strength Metallic Fibre Hybrid Spun Yarns - Amir Shahzad; Muhammad Bilal Qadir; Zulfiqar Ali; Zubair Khaliq; Muhammad Qamar Khan; Ick-Soo Kim (Applied Sciences, 2022)
Stainless-steel fibre hybrid spun yarns are becoming increasingly popular due to their wide range of applications. In this aspect, the cost-effective and scalable processing of such yarns is highly important. Stainless-steel staple fibres are relatively heavier and weaker compared to conventional textile fibres. As a result, the staple spinning processing of these fibres showing higher tensile strength and productivity both at the same time is quite challenging. In this manuscript, we explored a number of spinning techniques to find the optimised method of producing low-twist and high-strength stainless-steel fibre hybrid spun yarns offering the advantage of both quality and productivity. Conventional ring spinning, folding and twisting, and advanced ring spinning techniques (ARSTs) such as pneumatic compact ring spinning and pneumatic compact SIRO spinning were employed in this study. Additionally, the plain and SIRO yarns were produced in two forms using the compact spinning method, one with pneumatic suction active (compact plain, compact SIRO) and other with pneumatic suction inactive (noncompact plain, noncompact SIRO). The tensile properties of yarns were tested and analysed. The results reveal that the tensile properties of conventional ring-spun and plied yarns can be enhanced to some extent by increasing the twist coefficient (TC) and the number of yarn plies, respectively. In contrast, by finding optimised spinning parameters, a substantially higher tensile strength (up to 16%) of yarns, produced at ARSTs, was observed even at the minimum level of TC used in experiments. The findings of the study are extremely valuable in terms of scaling up the production of high-quality metallic fibre hybrid spun yarns at a higher productivity level.